Bibliometric Analysis of Research in Digital Literacy using Google Scholar Database from 2017-2021 - Setyorini, Triyana Wahyu (Journal of Educational Technology and Instruction, 2022)
Bibliometrics is an analytical technique that functions as a communication tool for quantitative results. The theme of this bibliometric research is Digital Literacy. Digital literacy is the knowledge and skills of users in utilizing digital media. Technological developments are in line with the times, so digital literacy needs to be improved. This study use a bibliometric approach with a 5step method, there are 1) determining search keywords, 2) initial search results, 3) narrowing search results, 4) compiling statistics, and 5) analyzing data. There are 5 variables in this study, year of publication, keyword mapping, number of authors, author mapping, and citations. The results obtained are 999 articles with “digital literacy or digital literacies” as the theme in the Google Scholar database 2017-2021. The results of the data that have been analyzed, then mapped using the VosViewer application. The data for the trend of the most article titles was obtained, 249 articles in 2018. A total of 398 articles were written by a single author with the most influential authors being Castek, J. The keyword trends used in 2017-2021 are “digital literacy”, “information literacy”, “media literacy”, “information”, and “chapter”. Of the 999 articles, the title ‘The relation between 21st century skills and digital skills: A systematic literature review by the authors E. Van Laar, A. J. A. M. Van Deursen, J. A. G. M. Van Dijk, Jos de Haan which has the most citations, 873 citations.